2016
DOI: 10.1111/jne.12445
|View full text |Cite
|
Sign up to set email alerts
|

Does Dynorphin Play a Role in the Onset of Puberty in Female Sheep?

Abstract: Puberty onset involves increased GnRH release due to decreased sensitivity to oestrogen (E)-negative feedback. Because GnRH neurones lack E receptor alpha, this pathway must contain interneurones. One likely candidate is KNDy neurones (kisspeptin, neurokinin B, dynorphin). Our overarching hypothesis was that the prepubertal hiatus in LH release involves reduced kisspeptin and/or heightened dynorphin input. We first tested the specific hypothesis that E would reduce kisspeptin-immunopositive cell numbers and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 58 publications
4
38
1
Order By: Relevance
“…Around the time of puberty, the number of detectable PDYN neurons was lower than for KISS1 and TAC3 neurons, which is consistent with other data obtained in female sheep showing very few PDYN cells in the prepubertal ewe (Lopez et al, 2016). The striking difference in the number of neurons expressing TAC3 , KISS1 , and PDYN at this stage of development is interesting, considering that the three peptides co‐localized in the KNDy neurons in the adult sheep (Goodman et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Around the time of puberty, the number of detectable PDYN neurons was lower than for KISS1 and TAC3 neurons, which is consistent with other data obtained in female sheep showing very few PDYN cells in the prepubertal ewe (Lopez et al, 2016). The striking difference in the number of neurons expressing TAC3 , KISS1 , and PDYN at this stage of development is interesting, considering that the three peptides co‐localized in the KNDy neurons in the adult sheep (Goodman et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…The striking difference in the number of neurons expressing TAC3 , KISS1 , and PDYN at this stage of development is interesting, considering that the three peptides co‐localized in the KNDy neurons in the adult sheep (Goodman et al, 2007). This suggests that the neuroendocrine axis governing reproductive function is different in young and adult animals and, as suggested earlier (Lopez et al, 2016), a rise in progesterone levels may be necessary for induction of PDYN expression, perhaps explaining why the number of cells increased markedly in the rostral ARC, following puberty. In spite of the low number of cells, we showed that GDX reduced the number of PDYN cells.…”
Section: Discussionsupporting
confidence: 57%
“…45 A similar increase in LH pulse frequency and mean levels was observed in prepubertal female sheep treated with a KOR antagonist. 49 These findings are compatible with a repressive role of Dyn on kisspeptin output from ARC Kiss1 neurons also during puberty, in line with the original KNDy hypothesis in adulthood. 39 Of note, other members of the TAC family (and possibly endogenous opioid peptides other than Dyn) are likely to participate also in the modulation of puberty onset.…”
Section: Partners Of Kisspeptins For the Control Of Puberty: Kndy Neusupporting
confidence: 81%
“…Several neural substrates such as gamma amino butyric acid, neuroestradiol and β‐endorphin (β‐ENDO) are produced by neurones in the arcuate nucleus (ARC) of the medial basal hypothalamus (MBH) and are capable of inhibiting prepubertal GnRH release. Additionally, dynorphin (DYN), another peptide produced in the ARC, has also been shown to inhibit prepubertal GnRH and thus, luteinising hormone (LH) secretion . Other investigators have shown that the administration of anti‐DYN caused increased serum LH, and that a kappa opioid receptor (KOR‐1) antagonist increased the pulsatile secretion of LH and advanced puberty .…”
Section: Introductionmentioning
confidence: 99%